Applying Customer Orientation to IT Organizations - Al Qubaisi, Khaled Ahmed Hamel (2008)
The purpose of this dissertation is to investigate the various models used in the application of market orientation to different sectors and select an appropriate model to be examined and implemented within the IT organizations / departments to measure how market oriented they are and enhance their effectiveness in servicing their customers. The Methodology used in this dissertation is the model of Kohli and Jaworski (1990) and Jaworski and Kohli’s (1993) as an application of market orientation within the IT organizations / departments in the United Arab Emirates. This model consists of intelligence generation, intelligence dissemination and organization-wide- responsiveness. Case studies with four companies in the financial sector in the United Arab Emirates were used to examine this approach by conducting interviews as a method of data collection. The application of market orientation in IT organizations was suitable. It was found that IT organization seriously lack the concept of market orientation. In addition, barriers were identified which halted the application of market orientation. However, the organization selected are in the development stage of market orientation where couple of factors found could be enhanced, adjusted, and used as a base for implementation of market orientation.